(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the clinical and paraclinical characteristics of patients undergoing breast reconstruction using latissimus dorsi flap following mastectomy for stage I-II breast cancer at Military Hospital 175. Subjects and Methods: A descriptive cross-sectional study combined with a prospective approach was conducted on 46 patients diagnosed with stage I-II breast cancer who underwent breast reconstruction using a latissimus dorsi flap following mastectomy at Military Hospital 175, from January 2022 to October 2024. Results: The study included 46 patients with an average age of 48.3 ± 9.1 years, with the majority falling within the 40-59 age group (54.3%). Most patients were diagnosed at stage I according to the TNM classification (58.7%). Partial mastectomy was the most commonly performed surgery (43.5%), followed by total mastectomy (39.1%), with breast-conserving surgery accounting for the lowest rate (17.4%). Invasive ductal carcinoma was the predominant histopathological type (89.1%). Immunohistochemical analysis was performed in 82.6% of patients, with ER (+) and PR (+) detected in 63.2% and 68.4%, respectively; HER2 (-) accounted for 68.4%, and Ki-67 expression was evenly distributed between ≤14% and >14%, each at 50.0%. Conclusion: Clinical characteristics such as middle age, stage I-II disease, and the use of breast-conserving or partial mastectomy significantly support the efficacy of breast reconstruction using latissimus dorsi flap, optimizing aesthetic outcomes, functional recovery, and minimizing complications.